Does the radical GPRI strongly depend on the population scheme? A comparative study to predict radical attack on unsaturated molecules with the radical general-purpose reactivity indicator - Barrera, Yoshio (Journal of computational chemistry, 2024)
© 2024 Wiley Periodicals LLC.